Diabetic Ketoacidosis In Children: From Early Recognition To Optimal Management (The Review of Diabetic Studies, 2025)
Diabetic ketoacidosis is an acute complication of diabetes associated with severe metabolic impairment. The condition is commonly encountered in the pediatric diabetic population and necessitates prompt response by the parents and the healthcare team. Education about the condition and the various clinical features helps in providing expedited care to the children.Aim: To objectively review the latest methodology for treatment guidelines for the management of diabetic ketoacidosis in pediatric patients.Materials and methods: This review is a comprehensive search of PUBMED from the year 2015 to 2025.Conclusion: Diabetic ketoacidosis is a medical emergency that is involved with mortality and morbidity in pediatric patients. Management of patients with DKA requires expeditious and accurate diagnosis and treatment regimen establishment. It is essential to be up to date with the latest therapy guidelines and treatment modalities to minimize the risk of loss of life and the economic costs associated with prolonged hospital stays for managing complications.